International Perspectives on Autism Therapy: Practices in Germany’s Die Lebensgemeinschaft and Indonesian Foundations - Alin Greenawati Cavelius; Franz Hessel; Vaibhavi Dargude (Universitas Negeri Semarang, 2025)
Global approaches to Autism Spectrum Disorder (ASD) vary, with increasing emphasis on inclusive practices and cross-cultural research for effective solutions. This study addresses the challenges surrounding the treatment and societal acceptance of children with ASD, particularly focusing on the transition from childhood to adulthood. It explores the initial emotional reactions of parents upon receiving an autism diagnosis and examines how foundations, schools, and clinics manage the care and treatment of children with ASD, emphasizing early and appropriate therapeutic interventions. The research compares the treatment of children with autism in Indonesia and adult individuals with autism in Germany. A mixed-methods approach, combining quantitative and qualitative methods, was employed, including a literature review on Indonesian autism research centers and in-depth interviews with experts from a special school and private therapy clinics in Indonesia. The study examines both beneficial and detrimental aspects of autism treatment, revealing societal misconceptions that perceive autism as a detriment, with therapeutic interventions viewed as the primary means of amelioration. Despite challenges, such as workforce limitations in educating children with autism, the study draws attention to the potential benefits of community-based initiatives in Germany, specifically the employment opportunities at Werkstätten (workshops), as a model for sustainable inclusion for individuals with autism in Indonesia. The research emphasizes the importance of such programs in enhancing autism literacy and preparing educators to foster better practices in young learners, ultimately contributing to the advancement of early childhood education across different cultural contexts.